Threshold concentration of chlorides in concrete for stainless steel reinforcement: Classic austenitic and new duplex stainless steel. (20th October 2018) - Pachón-Montaño, A.; Sánchez-Montero, J.; Andrade, C.; Fullea, J.; Moreno, E.; Matres, V.
Highlights: A relationship between threshold concentration of chlorides and PRE values is shown. The corrosion rate depends on chloride concentration for specific cement. A new methodology has been developed to avoid the steel rebars polarization. Calculations of service life have been made for a specific exposure conditions. Abstract: Stainless steel rebars is used to lengthen the service life of structures in aggressive media. Corrosion resistance was studied in five grades of mortar-embedded stainless steel: EN 1.4307, EN 1.4404, EN 1.4482, EN 1.4362 and EN 1.4462. A modified accelerated chloride attack was applied to prevent steel rebar polarisation and artificial re-passivation. The critical chloride concentration was determined. Based on corrosion rate, service life was calculated for a given exposure at two probability levels.